Effects of bund crops and insecticide treatments on arthropod diversity and herbivore regulation in tropical rice fields - Horgan, F.G.; Ramal, A.F.; Villegas, J.M.; Jamoralin, A.; Bernal, C.C.; Perez, M.O.; Pasang, J.M.; Naredo, A.I.; Almazan, M. L. P. (Wiley, 2017)
Ecological engineering using vegetable or flower strips is promoted as a potential pest management strategy in irrigated rice. Farmers in the Philippines often plant rice levees (bunds) with vegetables, particularly string beans (Vigna unguiculata [L.] Walpers) to supplement income, but without considering the potential for pest management. This study examines the effects of planted bunds on rice herbivores and their natural enemies. We compared arthropods in (a) rice fields that had string beans planted on bunds, (b) fields without string beans and without any insecticide applications and (c) fields without string beans but with insecticide treatments (standard practice). Rice yield was similar across all treatments; however, the vegetation strips produced an extra 3.6 kg of fresh string bean pods per metre of bund. There were no apparent increases in major natural enemy groups in fields with string beans compared to fields with conventional bunds. Fields with insecticide treatments had higher damage from leaffolders (Lepidoptera: Pyralidae). The sprayed fields also had lower parasitism of planthopper eggs and fewer predatory dragonflies and damselflies (Odonata). Furthermore, the mortality of planthopper (Delphacidae: Hemiptera) and stemborer (Pyralidae) eggs by parasitoids and predators was density dependent only in the unsprayed fields (with and without string beans). Our results demonstrate that planting string beans on rice bunds improves the productivity of rice farms, but our ecological engineering system did not appreciably affect natural enemy or herbivore abundance; however, chemical insecticides adversely affected pest regulatory ecosystem functions leading to higher pest damage.